IMPROVING STUDENT LEARNING OUTCOMES THROUGH THE APPLICATION OF THE PAIRED STORY TELLING METHOD IN MY IDOL RECOUNT TEXT MATERIAL IN CLASS X MIPA 1 SMA NEGERI 1 GEDEG - Lestari Wijayati (Sean Institute, 2022)
Foreign language learning such as English subjects need to be given in an appropriate manner earnest , interesting and fun, so that the completeness of learning outcomes can be achieved. The results of initial observations at Gedeg 1 Public High School obtained the daily test scores for class X MIPA 1, totaling 3 2 students , who did not complete the study amounted to 1 2 students with a completeness percentage of 37.5%. The low learning outcomes are due to the application of inappropriate learning methods, passive students in learning, no assessment of assignments. Therefore, a class action research (PTK) was conducted with the aim of this study to analyze the increase in learning outcomes for class X SMA Negeri 1 Gedeg through the application of paired story telling learning methods . Classroom action research was conducted in two cycles. Each cycle consists of the stages of planning, implementing, observing and reflecting. The subjects of this study were students of SMA Negeri 1 Gedeg Class X for the 2019/2020 academic year consisting of 32 students . The data collection instruments in this study were evaluation questions for the cognitive domain which were carried out at the end of each cycle and observation sheets for the affective and psychomotor domains. Based on the results and discussion it can be concluded that learning uses the paired story telling method providing convenience for teachers in learning, making learning centered on students, completing learning outcomes, and being able to teach and train students' character behavior. The implementation of lesson plans was in good category with an average score of 3.0 in the first cycle and 3.27 in the second cycle. Student activity reached 85.26% in the first cycle and rose to 92.22%. In the aspect of scientific behavior both cycles are in the good category. Mastery learning outcomes also showed an increase, from 75% in the first cycle to 90.63% in the second cycle.